ANALISIS PENGARUH ORIENTASI KEWIRAUSAHAAN DAN KOMPETENSI ASPEK PENGETAHUAN DAN KETRAMPILAN TERHADAP KINERJA PEMASARAN DI PENGRAJIN PANDE BESI KABUPATEN MADIUN - Lestari, Sri Setijasih; M.Stats, Siswandari; Riani, Asri Laksmi (Jurnal Pendidikan Insan Mandiri, 2015)
The objective of this research is to investigate how far the correlation between entrepreneurship orientation and competency of knowledge and skill aspects on marketing performance of blacksmith craftsmen in Madiun Regency. This research used the survey method with the quantitative analysis approach with associative problem formulation. The samples of research were taken by using the saturated sampling technique for the population number was relatively small, namely: 30. The data of research were gathered through questionnaire. They were then processed and analyzed by using the computer program of SPSS 16 for Windows. The result of research shows that the variables of entrepreneurship orientation and competency of knowledge and skill aspects significantly influence the marketing performance as indicated by the value of Fcount = 45.624 with the significance value = 0.000 < 0.05, meaning that the two variables, entrepreneurship orientation and competency of knowledge and skill aspects, have a positively significant effect on the variable of marketing performance. Due to the significant effect of each variable, the blacksmith craftsmen in Madiun Regency are encouraged to improve their entrepreneurship orientation and competency of knowledge and skill aspects so as to improve the marketing performance of their business operation.Keywords: Entrepreneurship orientation, competency, and marketing performance